Construction of continuous proton‐conduction channels through polyvinylimidazole nanotubes to enhance proton conductivity of polymer electrolyte membrane. Issue 8 (8th October 2018) - Hou, Jinghe; Sun, Xiang; Gu, Xinxin; Liu, Shanshan; Xiao, Zhenyu; Liu, Gang; Ding, Huili
ABSTRACT: Proton‐exchange membranes (PEMs) with high proton conductivity and low cost are crucial for the commercial promotion of proton‐exchange membrane fuel cells. In this study, inspired by the mechanism of plant ducts transporting moisture and biological proton transfer, polyvinylimidazole nanotubes (PVINTs) are prepared by a simple template method and then incorporated into a sulfonated poly(aryl ether sulfone) (SPES) matrix to fabricate composite membranes (SPES/PVINTs‐ X, where X is PVINT content in percent). The membranes were fully characterized using field emission scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and mechanical testing. The results indicated that the incorporation of PVINTs could improve the mechanical performance and dimensional stability of the membranes. In particular, the SPES/PVINTs‐7.5 composite membrane achieves remarkable results of proton conductivity of 0.212 S/cm under fully hydrated conditions at 80 °C, which is 56% higher than that of the SPES membrane. The construction of proton‐transfer channels through polymer nanotubes described in this paper may provide new insights into the preparation of composite proton‐exchange membranes. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47106. Abstract :